IL-17 and IL-22 are pivotal cytokines to delay wound healing of S. aureus and P. aeruginosa infected skin - Lecron, Jean-Claude; Charreau, Sandrine; Jégou, Jean-François; Salhi, Nadjet; Petit-Paris, Isabelle; Guignouard, Emmanuel; Burucoa, Christophe; Favot-Laforge, Laure; Bodet, Charles; Barra, Anne; Huguier, Vincent; Mcheik, Jiad; et al. (Frontiers in Immunology, 2022)
Introduction: Although the presence of pathogens in skin wounds is known to delay the wound healing process, the mechanisms underlying this delay remain poorly understood. In the present study, we have investigated the regulatory role of proinflammatory cytokines on the healing kinetics of infected wounds. Methods: We have developed a mouse model of cutaneous wound healing, with or without wound inoculation with Staphylococcus aureus and Pseudomonas aeruginosa, two major pathogens involved in cutaneous wound bacterial infections. Results: Aseptic excision in C57BL6/mouse skin induced early expression of IL-1β, TNFα and Oncostatin M (OSM), without detectable expression of IL-22 and IL-17A/F. S. aureus and P. aeruginosa wound inoculation not only increased the expression of IL-1β and OSM, but also induced a strong cutaneous expression of IL-22, IL-17A and IL-17F, along with an increased number of infiltrating Th17 cytokine-expressing cells. The same cytokine expression pattern was observed in infected human skin wounds. When compared to uninfected wounds, mouse skin infection delayed the wound healing process. Injection of the five cytokines in the wound edges induced delayed wound healing similar to that induced by the bacterial infection. Wound healing experiments in infected RAG2 KO mice (deficient in lymphocytes) showed a wound healing kinetic similar to uninfected RAG2 KO mice or wild type mice. RAG2 KO infected-skin lesions expressed IL-1β and OSM, whereas expression of IL-17 and IL-22 was weak or undetectable, confirming that the expression of these Th17 cytokines in this model is dependent on T cells. Wound healing was not delayed in infected IL-17R/IL-22KO, comparable to uninfected control mice. Injection of recombinant IL-22 and IL-17 in infected wound edges of RAG2 KO mice re-establish the delayed kinetic of wound healing, as in infected wild-type mice. Conclusion: These results demonstrate the synergistic and specific effects of IL-22 and IL-17 induced by bacterial infection delay the wound healing process, regardless of the presence of bacteria intra se. Therefore, these cytokines play an unexpected role in delayed skin wound healing.